Investigation of the optimum conditions for adsorptive hydrogen storage - Glante, Stephan; Fischer, Marcus; Hartmann, Martin (Emergent Materials, 2021)
Cryogenic adsorption using microporous materials is one of the emerging technologies for hydrogen storage in fuel cell vehicles. Metal-organic frameworks have been identified as suitable adsorbents exhibiting large hydrogen sorption at 77 K. With respect to technical realization, in this work, the deliverable capacity at the optimal storage temperature was determined for a series of MOFs in comparison to zeolite Ca-A. The deliverable capacity is defined as the amount of hydrogen released between a maximum tank pressure and a minimum back pressure and shows a maximum which defines the optimum operating temperature. This optimum operating temperature depends on the pore size of the adsorbent and the chemical properties of the surface. A number of materials are identified that exhibit optimal operating temperatures well above 100 K. A higher optimal storage temperature, however, typically results in a lower deliverable capacity.
CRIS-Team WoS Importer:2021-07-23